The Indian Forester. (February 2019) - Indian Council of Forestry Research and Eduction (Dehrdun India : Indian Council of Forestry Research and Eduction, 2019)
The Indian Forester is a Fountain of Information and learning which nourishes and enlightens the entire community's of foresters and scientists on scientific forestry and allied disciplines in the country. During its career of 140 years, it has taken an honorable place as one of the world's pioneers in Scientific Forestry. It is the oldest journal on tropical forestry and has been very closely associated with the science of forestry with distinction for the country. The issues of 140 years (Vol.1 to 140) have published thousands articles on all aspects of scientific forestry.